1992
DOI: 10.1111/j.1365-2249.1992.tb05855.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4-independent binding of HIV-1 to the B lymphocyte receptor CR2 (CD21) in the presence of complement and antibody

Abstract: SUMMARYComplement and antibody contribute to infection-enhancement and possible expanded cellular tropism of HI V-1 in vitro through a process requiring complement receptors. Until now, however, the ability of HIV-1 to bind complement receptors has not been documented or characterized. We investigated whether antibody and complement permitted HIV-1 to bind to the B lymphocyte receptor, CR2 (CD21), in an effort to learn more about infection-enhancement, and also because CR2 can mediate B cell proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…V1V2-specific complement-activating antibodies were measured as a function of C3d deposition on a panel of gp70-V1V2-coated beads. C3d was chosen for detection because it has been used previously to quantify complement activation [ 50 ], and because it is a dominant C3 cleavage fragment on complement-opsonized HIV-1 virions as determined in CD21-dependent binding experiments [ 42 , 43 ]. Carboxylated beads were coated with either gp70 as a control for nonspecific activity, or with gp70 scaffolds containing the V1V2 domains of the gp120 vaccine immunogens used in RV144 (92TH093, A244 and MN) ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…V1V2-specific complement-activating antibodies were measured as a function of C3d deposition on a panel of gp70-V1V2-coated beads. C3d was chosen for detection because it has been used previously to quantify complement activation [ 50 ], and because it is a dominant C3 cleavage fragment on complement-opsonized HIV-1 virions as determined in CD21-dependent binding experiments [ 42 , 43 ]. Carboxylated beads were coated with either gp70 as a control for nonspecific activity, or with gp70 scaffolds containing the V1V2 domains of the gp120 vaccine immunogens used in RV144 (92TH093, A244 and MN) ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additional soluble factors, such as complement factor H, may further contribute to the ability of HIV-1 to evade complement lysis [ 38 , 39 ]. In the absence of lysis, complement-opsonized HIV-1 is free to bind a variety of complement receptor-bearing cells, most notably cells expressing either CR1/CD35 [ 40 , 41 ] or CR2/CD21 [ 42 44 ]. Cellular interactions of complement-opsonized HIV-1 could have a number of consequences that may be either beneficial or harmful to the host [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies implicated complement activation in HIV-1 infection enhancement ( 23 29 ). More recently, it has been reported that complement-opsonized virus promotes viral establishment in colorectal mucosa ( 30 ) and infection of mucosa-resident Langerhans cells ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another virus that exploits CR2 as a receptor for viral entry is the human immunodeficiency virus 1 (HIV-1) ( 84 ). HIV-1 can infect B cell lymphocytes in a complement/C3-dependent and CD4-independent manner, thus facilitating viral dispersion and access to lymphoid organs ( 85 ). Besides viruses, the pathogenic yeast Cryptococcus neoformans has been shown to use an extracellular factor, the antiphagocytic protein 1 (App1), to bind to CR2 (and also CR3) and avoid complement-mediated phagocytosis by alveolar macrophages ( 86 ).…”
Section: Highly Modular Complement Receptors Based On the Ccp/scr Domainmentioning
confidence: 99%